2010
DOI: 10.1177/117954681000400001
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Study on how Far Anger Contributes to Initiating Essential Hypertension in Canadian Caucasian Adults with a Family History of Hypertension

Abstract: The goal of the present correlational study is to test the hypothesis that anger initiates essential hypertension in Canadian Caucasian adults with a family history of hypertension. The study population will include a cohort of 100 men and women aged 25 to 45 years at enrollment recruited from the University of Ottawa General and Civic Hospitals. Participants who are normotensives will be included in the study given that they have a family history of hypertension. The Spielberger State Trait Anger Expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…This is not surprising as Shehata et al 5 found relatives of hypertensive subjects to be more likely to have HTN early in life 5. The risk of occurrence of HTN was found to be greater in subjects with hypertensive first-order family members 27…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is not surprising as Shehata et al 5 found relatives of hypertensive subjects to be more likely to have HTN early in life 5. The risk of occurrence of HTN was found to be greater in subjects with hypertensive first-order family members 27…”
Section: Discussionmentioning
confidence: 92%
“…In some Arab countries HTN has become a major health problem 4. This drastic increase in incidence of HTN is specifically caused by a combination of many parameters, including family history,5 change in lifestyle, dietary habits and environmental factors 6…”
Section: Introductionmentioning
confidence: 99%
“…Essential hypertension has a multifactorial aetiology, and many studies have highlighted the influence of psychological factors both in the general increase of blood pressure and in the possible development and maintenance of hypertension. Specifically, the role of anger (Shehata, 2010), anxiety and depression (Rafanelli, Offidani, Gostoli, & Roncuzzi, 2012;Rubio-Guerra et al, 2013), acute stress (e.g., traumatic life events), negative emotions (Spruil, 2010) and type D personality (Grande, Romppel, & Barth, 2012) are well known.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Global analysis showed that the number of people with uncontrolled hypertension (>140/90 mm of Hg) increased from 600 million in 1980 to nearly 1 billion in 2008 and this number is expected to rise to 1.56 billion by 2025, which means 29% of the world adult population will have hypertension. [7] This serious increase in the incidence of hypertension is significantly associated with a combination of many factors, including family history, [8] lifestyle, dietary habits and environmental factors. [9] In Saudi Arabia, hypertension is increasing in prevalence affecting more than one fourth of the Saudi population.…”
Section: Introductionmentioning
confidence: 99%